Symplectic Non-Squeezing for the Cubic NLS on the Line. (20th July 2017) - Killip, Rowan; Visan, Monica; Zhang, Xiaoyi
Abstract: We prove symplectic non-squeezing for the cubic nonlinear Schrödinger equation on the line via finite-dimensional approximation.